The curvilinear effect of benevolent leadership on team performance: The mediating role of team action processes and the moderating role of team commitment. Issue 3 (6th April 2018) - Li, Guiquan; Rubenstein, Alex L.; Lin, Weipeng; Wang, Mo; Chen, Xingwen
Abstract: Leaders are encouraged to show benevolence to followers in paternalistic cultures. Yet, there remains debate about whether the influence of increasingly benevolent leadership on follower outcomes is linearly favorable. Grounded in the too‐much‐of‐a‐good‐thing effect and resource allocation theory, we developed and tested a model considering a potential curvilinear relationship between benevolent leadership and team performance while also examining the mediating role of team action processes. We further reasoned that this curvilinear indirect effect would be moderated by team commitment, which could neutralize the diminishing performance returns resulting from excessive benevolent leadership. To test these ideas, we carried out two studies. In the first study, multisource and time‐lagged data collected from 381 employees working in 104 research and development teams showed that benevolent leadership exhibited an inverted U‐shaped relationship with team performance, but this curvilinear relationship disappeared in teams with high team commitment. In the second study, we replicated and extended our results using a sample of 417 employees from 101 hotel management teams of a large hotel chain. Specifically, we found an inverted U‐shaped relationship between benevolent leadership and team action processes, which mediated the inverted U‐shaped relationship between benevolent leadership and team performance. Moreover, this indirect curvilinear effect only held in teams with low team commitment. We discuss the implications of our findings for both theory and practice.